1999
DOI: 10.1007/s004649900966
|View full text |Cite
|
Sign up to set email alerts
|

Pneumoperitoneum from an eroded T-fastener

Abstract: We present a case of late gastric perforation caused by retained T-fasteners after removal of a percutaneous endoscopic gastrostomy tube. We emphasize that timely removal of these fasteners is important in preventing this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
5
0
2
Order By: Relevance
“…This is again dependent on PEG tube design and ease of removal. Cases of major complications due to retained T-fasteners have been reported, including patent sinus tract formation around the fixation sutures resulting in pneumoperitoneum [20]. Therefore, the use of this fixation method also does not entirely prevent major complications after PEG tube placement and again does not prevent the major complication of PEG dislodgement itself.…”
Section: Discussionmentioning
confidence: 99%
“…This is again dependent on PEG tube design and ease of removal. Cases of major complications due to retained T-fasteners have been reported, including patent sinus tract formation around the fixation sutures resulting in pneumoperitoneum [20]. Therefore, the use of this fixation method also does not entirely prevent major complications after PEG tube placement and again does not prevent the major complication of PEG dislodgement itself.…”
Section: Discussionmentioning
confidence: 99%
“…The suture maintains adequate strength for wound closure until 3 weeks, becoming completely absorbed between 90 to 110 days. The advantage of an absorbable suture is that it does not have to be intentionally severed in follow-up and will not leave a permanent foreign body leading from the gastric lumen to the skin, which could serve as a nidus for fistula 11. Accordingly, we found that significantly more t-fasteners had detached and passed through the gastrointestinal tract in the long term compared to short term.…”
Section: Discussionmentioning
confidence: 73%
“…A single case report described the complication of intraperitoneal leakage of gastric contents due to a sinus tract caused by a nonabsorbable t-fastener suture 11. In this case, the gastrostomy tube was removed 3 weeks prior to presentation for an acute abdomen and the gastropexy had been performed 7 months prior.…”
Section: Discussionmentioning
confidence: 99%
“…Although mostly innocuous, T-fasteners have been associated with major late complications. 8 While attempting to extract an old pull-throughtype gastrostomy tube, the internal head may get separated from a deteriorated stem and be retained within the stomach. This head can travel through the pylorus into the small bowel where it may become stuck and cause intestinal obstruction.…”
Section: Discussionmentioning
confidence: 99%